2001
DOI: 10.1103/physrevc.65.015201
|View full text |Cite
|
Sign up to set email alerts
|

Kaon photoproduction: Background contributions, form factors, and missing resonances

Abstract: The photoproduction p(␥,K ϩ )⌳ process is studied within a field-theoretic approach. It is shown that the background contributions constitute an important part of the reaction dynamics. We compare predictions obtained with three plausible techniques for dealing with these background contributions. It appears that the extracted resonance parameters drastically depend on the applied technique. We investigate the implications of the corrections to the functional form of the hadronic form factor in the contact ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 22 publications
1
85
1
Order By: Relevance
“…It is obvious that significant improvement in the χ 2 would be obtained once we included this resonance, especially when the S 01 (1800) is used. This result corroborates the finding of Janssen et al [6], since the large hadronic cut-off requires another mechanism to damp the cross section at high energies. This is achieved by a destructive interference between the hyperon resonance contribution and other background terms.…”
Section: Effects Of the Hyperon Resonancesupporting
confidence: 92%
See 2 more Smart Citations
“…It is obvious that significant improvement in the χ 2 would be obtained once we included this resonance, especially when the S 01 (1800) is used. This result corroborates the finding of Janssen et al [6], since the large hadronic cut-off requires another mechanism to damp the cross section at high energies. This is achieved by a destructive interference between the hyperon resonance contribution and other background terms.…”
Section: Effects Of the Hyperon Resonancesupporting
confidence: 92%
“…Later, Janssen et al [6] found that the use of hyperon resonances S 01 (1800) and P 01 (1810), simultaneously, is desired in order to obtain the hadronic form factor cut-off greater than 1500 MeV in their model. The larger value of cut-off is desired in the kaon photoproduction because they argued that the value of 800 MeV found in Ref.…”
Section: Effects Of the Hyperon Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…The hadron structure in the strong vertexes is taken into account by means of the dipole type form factors [5] introduced in the gauge-invariant way as proposed by Davidson and Workman [9].…”
Section: Formalism Of Isobaric Modelsmentioning
confidence: 99%
“…Most of the models have, however, problems with a reasonable description of new experimental data collected in JLab and Bonn [1]. Among the models which can still provide a satisfactory prediction in comparison with new data are the latest isobaric ones, Saclay-Lyon [2,3], Kaon-MAID [4], and Janssen et al [5].…”
Section: Introductionmentioning
confidence: 99%